2016
DOI: 10.4103/0971-5916.178617
|View full text |Cite
|
Sign up to set email alerts
|

Substance abuse amongst the medical graduate students in a developing country

Abstract: Background & objectives:Substance abuse is found worldwide including among students. We carried out this study to estimate the prevalence of substance abuse among medical student studying in a medical college in north India.Methods:Using a validated questionnaire a cross-sectional survey was conducted among 230 undergraduate and postgraduate medical students in a private medical college.Results:The prevalence of substance abuse was 20.43 per cent (47/230) among medical students. An increase in substance abuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 11 publications
2
57
3
Order By: Relevance
“…In addition, admission to a university is recognized as a time of particular vulnerability to drug abuse [ 25 ]. Other studies have also shown that the onset of drug abuse among students was mainly in the first year of university education, although the following years were also associated with an increase in drug abuse [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, admission to a university is recognized as a time of particular vulnerability to drug abuse [ 25 ]. Other studies have also shown that the onset of drug abuse among students was mainly in the first year of university education, although the following years were also associated with an increase in drug abuse [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study among freshmen college students in the US showed that hookah use in the past 30 days increased in the first academic year, and the highest prevalence of hookah use onset was in the first 2 months of academic instruction [ 25 ]. Freshmen are especially vulnerable to drug abuse [ 25 ], and the onset of drug abuse among students is typically in the first year of college [ 26 ], although the following years witness further increases in drug abuse [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common mental disorders affecting students are anxiety disorders, particularly in women [60], and they also report higher levels of stress than men [71]. Seventy-five to ninety percent of medical students, including nursing, increase alcohol and tobacco consumption particularly in the last year of their medical education [72]. Most of the cases (72%) feel a state of emotional well-being that helps to cope with the experienced psychological stress they are exposed to, despite being aware of the consequences of excessive alcohol and tobacco consumption [72].…”
Section: Stress and Mental Disordersmentioning
confidence: 99%
“…Seventy-five to ninety percent of medical students, including nursing, increase alcohol and tobacco consumption particularly in the last year of their medical education [72]. Most of the cases (72%) feel a state of emotional well-being that helps to cope with the experienced psychological stress they are exposed to, despite being aware of the consequences of excessive alcohol and tobacco consumption [72]. Something similar has been reported in nursing students, where stress, environmental influences, social acceptance, and easy availability of alcohol, as well as anxiety generated by the difficulty of the educational program, are factors that increase alcohol consumption in this population [73].…”
Section: Stress and Mental Disordersmentioning
confidence: 99%
“…Overall, the prevalence of substance use among health care students ranges from 5% to 67% [ 8 14 ], with higher percentages (67%) being reported in developed countries like the United States [ 8 ]. Among developing countries, such as Iran [ 9 , 10 ], Ethiopia [ 11 ], Nepal [ 12 , 13 ], and India [ 14 ] substance use among health care students varies from 5% to 48%. Moreover, 91.7% of the medical students using illicit substances admitted using them despite knowing their ill effects and the legal consequences [ 14 ].…”
Section: Introductionmentioning
confidence: 99%